Access to preventive care services and stage at diagnosis in head and neck cancer. Issue 10 (3rd July 2020) - Farquhar, Douglas R.; Lenze, Nicholas R.; Masood, Maheer M.; Divaris, Kimon; Tasoulas, Jason; Blumberg, Jeffrey; Lumley, Catherine; Patel, Samip; Hackman, Trevor; Weissler, Mark C.; Yarbrough, Wendell; Zanation, Adam M.; et al.
Abstract: Background: Decreased access to preventive care services has been proposed as a mechanism for the association between low socioeconomic status (SES) and advanced stage at diagnosis in patients with head and neck squamous cell carcinoma (HNSCC). Methods: Retrospective analysis of patients diagnosed with HNSCC in North Carolina between 2002 and 2006. Results: A total of 1108 patients with HNSCC were included in the study. In the multivariable analysis, use of annual routine dental services (OR 0.7, 95% CI 0.5‐0.9) and colonoscopy in the past 10 years (OR 0.7, 95% CI 0.5‐0.9) were associated with lower odds of advanced T stage at diagnosis. Having no insurance (OR 1.8, 95% CI 1.1‐2.9), an income <$20 000 (OR 1.6 95% CI 1.03‐2.6), and >10 pack‐years tobacco use (OR 1.5, 95% CI 1.04‐2.2) were associated with advanced T stage at diagnosis. Conclusion: Use of preventive care services and SES independently predict stage at diagnosis in HNSCC.